The Role Of Introvert And Extrovert Characters In English Language Subjects: A Qualitative Study: Peran karakter introvert dan ekstrovert dalam pelajaran bahasa inggris: sebuah studi kualitatif - Virga Putra Darma; Reni Apriani; Caskani; Khojanatun; Juniawan Ramadhan (Journal of Innovative and Creativity, 2026)
Communication plays an essential role in human interaction because through communication individuals can gain knowledge, build relationships, and exchange ideas. In the context of foreign language learning, the effectiveness of communication is influenced by students’ personality characteristics, particularly introvert and extrovert traits. Foreign language acquisition varies among learners and involves the mastery of four main skills: listening, speaking, reading, and writing. Therefore, students with different personality types tend to demonstrate different patterns of language acquisition, where extroverted learners are generally more open and expressive, while introverted learners tend to be more reserved. This study employed a descriptive qualitative method with a case study approach. The participants were 15 sixth-semester students of the English Education Department at Prima Bangsa Institute. Data were collected through interviews, classroom observations, and literature study to explore the role of introvert and extrovert personalities in English language acquisition. The results indicate that most participants displayed introverted personality traits, yet they still showed relatively good foreign language acquisition. Introverted students tended to listen more carefully and speak concisely, which contributed positively to their comprehension and language development, although limited vocabulary and pronunciation sometimes hindered fluency. Meanwhile, extroverted students were more active in verbal interaction but did not necessarily demonstrate superior language acquisition. In conclusion, introvert–extrovert personality differences do not solely determine students’ foreign language acquisition. Language development is also influenced by learners’ motivation, learning environment, and willingness to participate in communication activities.